Perbaikan Stasiun Kerja Packing untuk Menurunkan Keluhan Otot Rangka dan Meningkatkan Produktivitas Pekerja PT Y - Marvin Abraham; Herry Christian Palit (Jurnal Titra, 2020)
PT Y is a food company that produces wet pia, wet pia that is produced has a variety of flavors, one of which is chocolate, vanilla and others. This study aims to reduce the level of complaints in skeletal muscle and increase the productivity of workers at the packing station work station. Workers at the packing station have an average score of skeletal muscle complaints of 37.5 this value has a greater value than all departments in PT Y. This study uses data collection methods with the nordic body map questionnaire, finding the standard time of workers and analysis of total output, increasing the number of sales at PT Y. The analysis carried out aims to find out this research can solve existing problems or not. The results of this study indicate that the nordic body map method has a significantly reduced pain level in the muscles of the skeletal muscle, because the p-value is below 0.05. The standard time calculation method has decreased and increased productivity of workers with a value of 19.64 packs per hour to 23.16 packs per hour. This research can be a good investment because the total costs incurred do not affect the existing sales value.